Pengaruh Store Atmosphere, Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen pada PT. Pasar Swalayan Maju Bersama Medan - Jovan, Farrel; Vivian, Callista; Nasution, Isna Asdiani; Zuriani Hasibuan, Melisa (IPM2KPE, 2024)
PT. Pasar Swalayan Maju Bersama is part of the Maju Bersama Group which has 14 stores spread across various areas in the city of Medan. Based on the results of observations, researchers found a decrease in the number of consumers making purchases each year. As a result, stores that were previously crowded with visitors now look deserted. This phenomenon is caused by several factors, including store atmosphere, product quality, and service quality. The population in this study were all consumers who made purchases at the company during 2022, but the exact number is unknown. Therefore, researchers used the Lemeshow formula to determine the sample, and obtained 96 respondents. The sampling technique used was accidental sampling, where respondents were selected randomly. The results of the study showed that store atmosphere had a positive and significant effect on purchasing decisions, as well as product quality and service quality. Overall, store atmosphere, product quality, and service quality simultaneously had a significant effect on purchasing decisions Keywords: Product Quality, Service Quality, Purchase Decision, Store Atmosphere